Dinámica demográfica de la ciudad de León: un breve ensayo de interpretación (I) - Reguera Rodríguez, Antonio Teodoro (Estudios humanísticos. Geografía, historia y arte, 1988)
This paper will try to prove the following hypothesis: how the material world is reproduced in a social formation, and during a concrete historical period, and determines the repoduction processes of the work force. If one is dealing with a city, due to the very determining factors of the urban economy, the external demographic reproduction (migrations) is much more important than the internal (natural demographic balance). This conclusion is particularly true of phases of accelerated rhythm in urban growth.